Advances in Antenna Technology for Wireless Handheld Devices - Jaume Anguera (International Journal of Antennas and Propagation, 2013)
The constant evolution of wireless handheld devices together with the apparition of multiple wireless communication systems fosters the antenna community to design new radiating and measurements systems capable of satisfying the market demands. It is an object of the present paper to provide an overview of the evolution that wireless handheld technology has experienced in the last years. In this sense, a description of the evolution of wireless handheld devices, regulations, challenges in today’s smartphones, and handset characterization is reviewed. Finally, recent advances in antenna technology for wireless handheld or portable devices are presented.